2018
DOI: 10.1080/00918369.2018.1519304
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care Providers’ Attitudes, Practices, and Knowledge in Treating LGBTQ Communities

Abstract: Introduction: Cultural competency in lesbian, gay, bisexual, transgender, and queer (LGBTQ) healthcare has been found to be lacking within various medical specialties, but no studies have compared competency among primary care providers. Methods: The authors compared 127 primary care providers' cultural competency regarding LGBTQ health using a survey that assessed providers' attitudes, practices, and knowledge. Results: Overall, 78.0% of respondents agreed that they were comfortable treating LGBTQ patients. Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 21 publications
1
33
0
2
Order By: Relevance
“…On both the GLMA Provider Directory and OutCare Health OutList, which serve the general LGBTQ population, providers may list their particular subspecialties, e.g., having the ability to specify transgender expertise. Given that past research has shown that providers' funds of knowledge differ between general LGBTQ education and populationspeci c pro ciency (e.g., the transgender population) [12], it is paramount that provider directories specify…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On both the GLMA Provider Directory and OutCare Health OutList, which serve the general LGBTQ population, providers may list their particular subspecialties, e.g., having the ability to specify transgender expertise. Given that past research has shown that providers' funds of knowledge differ between general LGBTQ education and populationspeci c pro ciency (e.g., the transgender population) [12], it is paramount that provider directories specify…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of such LGBTQ disparities is multifaceted and appreciably a function of insu cient provider cultural competency. For example, both students and providers have been shown to harbor biases [8,9] and negative attitudes [1,2,10], infrequently inquire about sexual orientation and gender identity [11][12][13], and demonstrate shortcomings in education [12][13][14][15][16]. In addition, many LGBTQ patients encounter high rates of refusal of care and exposure to verbal and physical violence during healthcare physical examinations, which can subsequently lead to postponement of healthcare needs, delay in receiving medication, and avoidance of obtaining routine and urgent healthcare services altogether [1,17].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of provider trust and access to affordable screening and treatment exponentially increases the degree of HIV risk in the sexual networks of SMM. Lack of culturally and medically competent providers on issues relating to lesbian, gay, bisexual, transgender, queer, asexual, intersex, and others (LGBTQ+) health ( Institute of Medicine, 2011 ; Nowaskie & Sowinski, 2019 ) and individual-/community-level factors, such as heteronormative assumptions stemming from group-based, cisgender, heterosocial hierarchies ( Parrott, 2009 ; Ray & Parkhill, 2021 ), have resulted in mistrust and misinformation about health risks ( Jaiswal et al, 2020 ; Ramos et al, 2019 ) and have perpetuated racism and discrimination among minoritized groups ( Arscott et al, 2020 ; Quinn et al, 2019 ), leading to experiences of internalized homophobia.…”
Section: Sexual Orientation Concealmentmentioning
confidence: 99%
“…Gaps in knowledge and cultural competency of health and social care practitioners working with LGBT+ older adults need attention but are yet to be prioritized (Bell, Bern‐Klug, Kramer, & Saunders, 2010; Greene et al, 2018; Nowaskie & Sowinski, 2019).…”
Section: Introductionmentioning
confidence: 99%